Hepatic steatosis mediates the relationship between cholecystectomy and BMI increase: a population-based study - Cao, Ji; Mao, Wenjun; Jiang, Qian; Huang, Xiaowei; Tan, Yunyan; Zuo, Fei; Luo, Tianping (Frontiers in Medicine, 2025)
BackgroundCholecystectomy has been linked with adverse metabolic outcomes, but its specific association with body mass index (BMI) and the underlying mechanisms remain insufficiently understood. This study aimed to assess the impact of cholecystectomy on BMI and examine the mediating role of hepatic steatosis.MethodsA total of 7,452 adults were included in this cross-sectional analysis. Baseline demographic, clinical, and laboratory data were compared between participants with and without cholecystectomy. Multivariable linear regression was used to evaluate the relationship between cholecystectomy and BMI, with progressive adjustment for demographic, clinical, and metabolic-inflammatory confounders. Subgroup and stratified analyses, propensity score modeling, and causal mediation analysis were conducted to validate findings and elucidate potential mechanisms.ResultsParticipants with cholecystectomy were older (mean age 61.0 vs. 49.5 years), more likely to be female, and exhibited higher BMI (mean 31.8 ± 8.1 cholecystectomy group vs. 29.6 ± 7.3 non-cholecystectomy, p < 0.05) as well as increased prevalence of hypertension, diabetes, and markers of inflammation (all p < 0.05). Cholecystectomy was independently associated with higher BMI after adjustment for confounders (fully adjusted β = 0.84 kg/m2; 95% CI: 0.09–1.59; p = 0.027), a finding robust to propensity score methods (overlap weighting β = 0.91; 95% CI: 0.55–1.27; p < 0.001). Stratified analyses indicated a more pronounced BMI increase among younger patients ( ≤ 50 years, β = 2.3; 95% CI: 0.83–3.76; p = 0.002), with no significant difference observed across postoperative time intervals. Causal mediation analysis demonstrated that hepatic steatosis, quantified by controlled attenuation parameter (CAP), mediated approximately 46% of the association between cholecystectomy and increased BMI (ACME = 0.806 kg/m2, 95% CI: 0.321–1.314; p = 0.002), while a significant direct effect of cholecystectomy remained (ADE = 0.964, 95% CI: 0.131–1.801) in bootstrap validation.ConclusionsCholecystectomy is independently associated with increased BMI, particularly among younger adults, and this relationship is partially mediated by hepatic steatosis. These findings highlight the need for long-term metabolic monitoring and targeted interventions in patients undergoing cholecystectomy.